Extent, Pattern and Correlates of Depression in Urban Geriatric Subjects: Findings from Community Based Study. - Keshari, Priya; Shankar, Hari (Indian Journal of Community Medicine)
Background: Depression decreases an individual's quality of life and increases dependence on others. The declining physical potential familiar infrastructure and loss of peer may cause anxiety, stress, depression, etc., in geriatric population. Objectives: The objectives of this study were as follows: (A) to assess the extent and pattern of depression in study subjects and (B) to find out the correlates of depression in subjects. Materials and Methods: This cross-sectional study was conducted on 616 geriatric subjects selected by multistage sampling procedure from urban Varanasi, India. A predesigned, pretested proforma was used for collecting socioeconomic information. Depression status was assessed using the Geriatric Depression Scale. For analysis of data, SPSS version 22.0 was used. Chi-square and logistic regression were used for inferential purpose. Results: The overall prevalence of depression in geriatric subjects was 29.7%; 15.7% of subjects were not satisfied with life and 30% often felt helpless. The adjusted odds ratio (95% confidence interval) for depression was 4.54 (2.99-6.09) in subjects >70 years, 4.00 (2.45-6.54) for widowed, 1.95 (1.13-3.35) for widowers, 4.95 (2.02-12.07) for lower, and 3.17 (1.79-5.64) for upper-lower socioeconomic status. Conclusion: Nearly one-third of urban geriatric subjects had depression which was significantly enhanced by advancing age, loss of partner, and socioeconomic adversities.